"Wholesale" and/or "retail": Analysis on the Orientation of the Compilation of the General Provisions of Civil Law and Comment on Its Contents. (3rd July 2017) - Wang, Zhu; Gong, Jian
Abstract : General Principles of the Civil Law is orientated as "detailed retail of the contents of the General Provisions Volume of Civil Code" and "brief wholesale of the contents of the Specific Provisions Volumes of Civil Code". The "Compilation of Civil Code" is the last phase of the fourth time of drafting of Civil Code which follows the transfer from "wholesale" to "retail" in the third time of the drafting of Civil Code, and the Decision to Rule by of Law realizes the historical transfer from "retail" to "wholesale" in time. In essence, the amendment of Criminal Code in 1997 is "Compilation of Criminal Code". By reference to the "Compilation of Criminal Code", the compilation of Civil Code is the exercise of "Amendment Right" provided in Paragraph 3 of Article 62 of the constitution rather than "Enactment Right". Substantially, the legislative plan for the compilation of Civil Code in two steps is the "wholesale" of Civil Code in two steps, namely the first step "to wholly sell" the contents of the General Provisions Volume of Civil Code, that is the General Provisions of Civil Law. And the second step "to wholly sell" the contents of the Specific Provisions Volumes of Civil Code. The General Provisions of Civil Law has the dual natures of "wholesale" and "retail". Most of the articles of the General Provisions of Civil Law are the "wholesale" of the contents of the General Provisions Volume of Civil Code, which falls into "definite wholesale" and "temporary tentative wholesale". A few articles provisions of the General Provisions of Civil Law directly or indirectly "retail" the contents of the Specific Provisions Volumes of Civil Code, and are the legislative reaction to make response to political determination, social opinions and practical needs in time.